STUDENT DESIGN - TO DEVELOP TECHNOLOGICAL COMPETENCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses educational technologies and didactic support for the development of design and technological competence of students through technology lessons.